Probing the function of metazoan histones with a systematic library of H3 and H4 mutants - Zhang, Weimin (Dev Cell, 2018)
Replication-dependent histone genes often reside in tandemly arrayed gene clusters, hindering systematic loss-of-function analyses. Here, we used CRISPR/Cas9 and the attP/attB double-integration system to alter numbers and sequences of histone genes in their original genomic context in Drosophila melanogaster. As few as eight copies of the histone gene unit supported embryo development and adult viability, whereas flies with 20 copies were indistinguishable from wild types. By hierarchical assembly, 40 alanine-substitution mutations (covering all known modified residues in histones H3 and H4) were introduced and characterized. Mutations at multiple residues compromised viability, fertility, and DNA-damage responses. In particular, H4K16 was necessary for expression of male X-linked genes, male viability and maintenance of ovarian germline stem cells, whereas H3K27 was essential for late embryogenesis. Simplified mosaic analysis showed that H3R26 is required for H3K27 trimethylation. We have developed a powerful strategy and valuable reagents to systematically probe histone functions in D. melanogaster.